2018
DOI: 10.1111/crj.12772
|View full text |Cite
|
Sign up to set email alerts
|

High flow nasal cannulae oxygen therapy in acute‐moderate hypercapnic respiratory failure

Abstract: There was no difference of the 30-day mortality and intubation rate between HFNC and NIV groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 39 publications
6
132
1
3
Order By: Relevance
“…This finding agrees with the subgroup analysis of hypercapnia patients in their retrospective study of HFNC versus NIV for postextubation by Yoo et al (). In the recently published prospective study, Lee et al () reported the comparison of HFNC and NIV in COPD exacerbation with moderate hypercapnic acute respiratory failure (pH 7.25–7.35). They found that the 30‐day intubation rate and mortality were similar and patients’ ABGs were not significantly different between the two groups after 6 and 24 hr, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with the subgroup analysis of hypercapnia patients in their retrospective study of HFNC versus NIV for postextubation by Yoo et al (). In the recently published prospective study, Lee et al () reported the comparison of HFNC and NIV in COPD exacerbation with moderate hypercapnic acute respiratory failure (pH 7.25–7.35). They found that the 30‐day intubation rate and mortality were similar and patients’ ABGs were not significantly different between the two groups after 6 and 24 hr, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with standard oxygen therapy, HFNO reduces the need for intubation (42). Patients with hypercapnia (exacerbation of obstructive lung disease, cardiogenic pulmonary oedema), hemodynamic instability, multiorgan failure, or abnormal mental status should generally not receive HFNO, although emerging data suggest that HFNO may be safe in patients with mild-moderate and non-worsening hypercapnia (42,43,44). Patients receiving HFNO should be in a monitored setting and cared for by experienced personnel capable of performing endotracheal intubation in case the patient acutely deteriorates or does not improve after a short trial (about 1 hour).…”
Section: Remarkmentioning
confidence: 99%
“…Ample evidence from critical care medicine, neonatal intensive care, flight medicine, and diving physiology support this assertion. (Abdo, 2012, Allerdet-Servent, 2019, Aubier, 1980, Barlow, 1944, Hanson, 1996, Jing, 2019, Lee, 2018, Merriman, 1955, Ogino, 2016, Robinson, 2000, Westlake, 1958, Yang, 2018 As mentioned earlier, much research has been devoted to identifying contaminants entering the pilot's breathing apparatus. (Denola, 2011) In high performance military aircraft, the pressure required to drive gases into the pilot's breathing mask is typically provided by the aircraft engine.…”
Section: Co2 Narcosis As the Cause Of Upesmentioning
confidence: 99%